Tvorba obchodního systému založeného na strategii TRB - Šťastný, Filip (Vysoké učení technické v Brně. Fakulta informačních technologií, 2017)
Bakalářská práce se zaměřuje na tvorbu automatického obchodního systému pro devizový trh Forex. Systém je založený na principu time range breakoutu a silně přizpůsobitelný pomocí parametrů. Práce popisuje nezbytný teoretický základ, návrh strategie, implementaci v jazyce Easy language i optimalizace a backtesting v platformě Multicharts.

This thesis is focused on creation of automatical trading system for Forex exchange market. System is based on time range breakout principal and highly customizable by parameters. The thesis explains basic principals of trading on Forex, a designing of the strategy, an implementation of the strategy in Easy language, optimalizations and backtesting using Multicharts platform.
Building Trading System Based on Time Range Breakout
Keywords: Forex; automatický obchodní systém; technická analýza; time range breakout.; Forex; automatical trading system; technical analysis; time range breakout.